"Please hold for your connection": Determining points of interconnection for open access broadband - Rob Nicholls (International Telecommunications Society (ITS), 2011)
One of the early decisions facing a regulator in the context of an open access Next Generation Access networks (NGA) is the location of the points of interconnection to that NGA. This decision is one which needs to take into account the scope of the natural monopoly associated with an NGA and the extent to which there is the potential for competitive supply of transmission services (or backhaul) from access seeker points of presence to the NGA. The Australian NGA is called the National Broadband Network (NBN). This paper starts with the research question, where are the optimum sites for points of interconnection to the Australian NBN?. The paper commences by describing the architecture of the Australian NBN and considering some of the issues which arise from the fact that it is designed to be ubiquitous. The paper considers the issues that need to be considered in determining the extent to which there is a natural monopoly in transmission services as well as the effects on outcomes that arise from the existing deployment of infrastructure associated with the delivery of digital subscriber line broadband services based on unbundled local loops and line sharing services. The paper then moves to consider the requirements for consideration in the Australian regulatory context. This is summarised by the phrase long-term interests of end-users and the paper considers the interpretation of this phrase in the context of decisions on the number and location of points of interconnection. There is a review of the nature and extent to which operators in Australia contributed to the deliberations of the Australian regulator in determining the location of points of interconnection. In turn the paper then describes the actual approach taken in respect of the Australian NBN and the rationale behind those decisions. The final part of the paper describes the decision that was taken along with the rationale. It also examines the subsequent positions taken by stakeholders in respect of the points of interconnection to the Australian NBN.
Keywords: 330; Next generation access network; national broadband network; natural monopoly; transmission; point of interconnection; GPON